Síntese de aminochalconas e análogos arílicos como agentes antivirais, antifúngicos e inibidores de mieloperoxidase - Santos, Mariana Bastos dos [UNESP] (2015)
Chalcones are open chain flavonoids. They show a broad range of biological activities. These compounds can be synthesized by several methodologies, mainly by ClaisenSchmidt condensation. Hepatitis C is a disease of great incidence in worldwide population, and according to its severity can lead to hepatocellular carcinoma. Paracoccidioidomycosis is a systemic mycosis caused by Paracoccidioides brasiliensis, and has a great incidence in Brazil, in imunodefficient pacients, its acute form can lead to commitment of organs such as spleen and liver. Myeloperoxidase (MPO) is an essential enzyme in imune response against patogen invasion. However, the MPO activity has been correlated with some endotelial disfunctions. The present work aimed the synthesis of three series of aminochalcones and the aryl analogues, with amino group at positions 2', 3' and 4' (ring A), and with donors and withdraw electron substituents on B ring. In order to evaluate the effects of the different positions of amino groups and the ring bioisosterism, these substances were evaluated for the inhibition of HCV replication, P. brasiliensis growth and clorinating MPO activity. The substances were synthesised with high yields, once 79% showed yield above 75%. Compound LQVM 22 was able to inhibit HCV replication in 41 %, at 2 µmol L-1. Compounds LQVM-16 and LQVM-17 demonstrated potent anti-P. brasiliensis activity, exhibiting MIC90 values of 0,49 µg mL-1. Compound LQVM-20 was the potentest inhibitor of MPO chlorinate activity, showing IC50 of 0,34 µmol L-1.Our chemical and biological studies of aminochalcones, and their aryl analogues led to the discovery of hits, which are valuable prototypes to developing of innovatives therapeutical agents...